Hubungan Kompetensi Sosial Guru dengan Gaya Mengajar Guru - Linda Wati; Hermi Yanzi; Berchah Pitoewas (FKIP Unila, 2017)
The purpose of this research to explain the relationship of social competence of teachers with teaching style of teachers in YP Unila High School in the academic year 2016/2017. The method used in this research is descriptive correlation method with quantitative approach with population of 60 responded. The main techniques of data collection by using questionnaires and their supporting techniques Is an interview. The independent variable in this study is the teacher's social competence while the dependent variable is the teacher's teaching style. Based on result of data analysis, it can be concluded that the relation of teacher social competence with teacher teaching style at YP Unila Senior High School in the academic year 2016/2017 in high category. Based on the results of data analysis test conducted, there is a very close and positive relationship between teacher social competence and teacher teaching style in YP Unila Senior High School academic year 2016/2017.Tujuan penelitian ini adalah untuk menjelaskan hubungan kompetesi sosial guru dengan gaya mengajar guru di SMA YP Unila tahun pelajaran 2016/2017. Metode yang digunakan dalam penelitian ini adalah metode deskriptif korelasi dengan pendekatan kuantitatif dengan populasi berjumlah 60 respnden. Teknik pokok pengumpulan data dengan menggunakan angket serta teknik penunjangnya. Adalah wawancara. Variabel bebas dalam penelitian ini adalah kompetensi sosial guru sedangkan variabel terikatnya adalah gaya mengajar guru. Berdasarkan hasil analisis data diperoleh kesimpulan bahwa hubungan kompetensi sosial guru dengan gaya mengajar guru di SMA YP Unila tahun pelajaran 2016/2017 dalam kategori tinggi. Berdasarkan hasil uji analisis data yang dilakukan, maka terdapat hubungan yang sangat erat dan positif antara kompetensi sosial guru dengan gaya mengajar guru di SMA YP Unila tahun pelajaran 2016/2017.Kata kunci: kompetensi sosial, gaya mengajar, guru.